Analys av högfrekvensstörningar och elnätskommunikation i distributionsnät - Påhlsson, Henrik (My University, 2009)
The use of Power Line Communication, PLC, as a communication solution for Automated Meter Reading, AMR, is popular by utilities in Sweden and other parts of the world due to demands of accurate and fast meter reading. However the use of the electrical grid as a communication medium is complex and sometimes problematic. This report handles some of the issues and problems that are important to understand when using the grid as a communications medium. Focus is mainly on investigating high frequency distortion in the Kristianstad power grid own by C4energi caused by a frequency converter. Measurements on site are done to investigate signal damping in the grid, different configurations for the frequency converter and signal strength of the PLC-system. The PLC-system that is used is an Echelon-system communicating on 75 kHz and 86 kHz. The results in this report can be applied to other systems communicating different frequencies in the CENELEC A-band. The results from the measurements show that the communication fails due to the frequency converter and that the noise level is too high. Tests done during the measurements show how some of the high frequency noise can be avoided by changing settings in the converter but this is not enough. An important result was that the problem can be to solved by changing the position for the PLC-concentrator further away from the converter another solution can be to add a filter to the frequency converter. COMSOL Simulations on connection cables are also done to analyze resistance due to skin effect at high frequency. The simulations are done to understand why stranded cables often works better then single stranded cables. The results from the simulations show clearly that it is better to use stranded cables then single stranded cables. The report is written in Swedish.
Keywords: Elkraftteknik; Electric power engineering